Multimedia applications: Graph algorithms visualization - Sevcikova, Andrea; Milkova, Eva (IEEE International Symposium on Computational Intelligence and Informatics, 2016)
Multimedia applications are nowadays often used to support and improve didactic processes across the wide range of education. There are specific subjects where the explanation and learning of the complex subject matter becomes a difficult task. This paper focuses on two important tools, program GrAlg and program A-DIMA developed at our university to enhance the Applied Informatics education, namely the area dealing with graph algorithms. These multimedia programs dealing with explanation of graph concepts and demonstration of graph algorithms serve as important means to support students logical thinking development as well as broadening their knowledge and connection to practice. Both tools are described in more detail in the paper.